Embryonic-like stem cell derived from adult bone marrow: immature morphology, cell surface markers, ultramicrostructure and differentiation into multinucleated fibers in vitro - Pang, R.; Zhang, Y.; Pan, X.; Gu, R.; Hou, X.; Xiang, P.; Liu, Z.; Zhu, X.; Hu, J.; Zhao, J.; Zhang, C. (Cellular and Molecular Biology, 2010)
Embryonic-like stem cell (ELSC), expressing part of surface markers of human embryonic stem cells, may be a better candidate for cell therapy of degenerative muscular disease than mesenchymal stem cell (MSC). We isolated ELSC and MSC from bone marrow, respectively, and compared their differences in the characteristics and the capacity of myogenic differentiation. Results showed that ELSC could be isolated successfully from 3 adult bone marrow samples by using serum-free medium with 10ng/ml basic fibroblast growth factor (bFGF). At the same cell density, MSC could also be isolated from the same samples by using DMEM/F12 medium containing 10% new cattle serum. However, ELSC appeared as small, morphologically slenderer, upregulated expression of SSEA-4 and ultramicroscopically more immature than MSC derived from the same samples. Immunofluorescent staining and RT-PCR analysis showed ELSC weakly expressed Oct-4, Nanog-3 and Sox-2. Moreover, ELSC and MSC could be induced into long, multinucleated fibers expressing myogenin and myosin heavy chain (MHC) in myogenic differentiation medium, but by day 10, proportion of multinucleated fibers positive for MHC was respectively 25.0%±6.9% and 13.8%±7.6% in ELSC and MSC culture. These data suggest that bone marrow derived ELSC represent an ideal candidate for cell therapy of degenerative muscular disease.